ANATOMICAL VARIANTS OF CELIAC TRUNK, HEPATIC AND RENAL ARTERIES IN A POPULATION OF DEVELOPING COUNTRY USING MULTIDETECTOR COMPUTED TOMOGRAPHY ANGIOGRAPHY - Arifuzzaman, Muhammad; Naqvi, Syeda Sawaira Nasim; Adel, Hatem; Adil, Syed Omair; Rasool, Mahreen; Hussain, Munawar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Multidetector Computed Tomography (MDCT)s has become a major part in evaluation of hepatic and renal tumours. With improvements in MDCT, CT angiography has also improved and normal anatomy and its variants in patients undergoing operative or interventional procedures can be effectively studied. The purpose of this study was to evaluate the frequency of anatomical variation of celiac trunk, hepatic and renal arterial systems in patients undergoing multidetector CT (MDCT) angiography of the abdominal aorta. Methods: A descriptive, retrospective cross-sectional study was carried out on CT angiographies performed during the months of October till December 2015. Hepatic and renal arteries and celiac trunk were studied and normal and anatomical variations were noted. All patients with abnormalities affecting the vessels or a history of any vascular abnormality were excluded from the study. Results: Out of total 110 patients, 69.1% had normal and 30.9% had variant hepatic artery with Michel Type IV being the most common variant whereas 88.2% had normal celiac trunk and 8.2% had gastrosplenic trunk variant. Variation in renal arterial system was observed in 15.5% of the patients with two renal arteries on right and two on left being the most common type. Multiple variants were identified in 11.8% of the patients. Conclusion: The type and knowledge of anatomy is of prime importance for an optimum preoperative planning in surgical or radiological procedure. MDCT allows minimally invasive assessment of arterial anatomy with high quality 3D reconstruction images. Keywords: Hepatic artery variant; Renal artery variant; Celiac trunk; Variations; Multidetector Computed tomography; MDCT